Tartil Method as an Effective Pedagogical Approach for Enhancing Students’ Interest in Quranic Learning - Engkizar Engkizar; Azhar Jaafar; Mohd Isa Hamzah; Syafrimen Syafril; M. Hidayat Ediz; Efendi Efendi; Arif Ridha; Afifah Febriani; Gifa Oktavia (Islamic Studies and Development Center in Collaboration With Students' Research Center Universitas Negeri Padang, 2026)
Quranic learning is often perceived as difficult by students, leading to low interest and limited engagement. However, with appropriate teaching methods tailored to learners’ diversity, motivation can be significantly improved. This study aims to analyze the impact of the Tartil method on enhancing students’ interest in Quranic learning. An exploratory sequential mixed-methods design was employed. Qualitative data were collected through in-depth interviews with fifteen informants (teachers and students) selected via purposive sampling, while quantitative data were obtained from 115 respondents using simple random sampling. Qualitative data were analyzed thematically using NVivo 12, while quantitative data were processed descriptively with SPSS 22. Findings revealed nine themes related to increased learning interest after applying the Tartil method. Quantitative analysis showed high student interest with a mean score of 4.14. These findings demonstrate that the Tartil method is a viable alternative for teachers in Quranic pedagogy, as it effectively fosters students’ motivation and engagement in Quranic learning.